Resolution of Marine Resource Disputes in Indonesia from the Perspective of Islamic Law and National Law - Abdul Hakim; Ainur Rahma (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
Indonesia, as an archipelagic country with a maritime territory covering more than two-thirds of its total territory, possesses enormous marine resource potential and is vulnerable to conflict. This study aims to analyze the dynamics of marine resource disputes in Indonesia and formulate a settlement model based on the integration of national law and Islamic legal principles. The study employed a qualitative method with a normative approach and literature studies from scientific journals, international legal documents, and Islamic legal literature. The results indicate that marine resource disputes in Indonesia are triggered by overlapping jurisdictional claims, illegal fishing practices, and weak law enforcement. UNCLOS 1982, as an international maritime law regime, has provided a normative framework, but its implementation is often hampered by political factors and economic interests. From an Islamic legal perspective, the principles of justice ('adl), benefit (maslahah), and the prohibition of overexploitation (Israf) offer a comprehensive ethical approach. The integration of these two legal systems has the potential to create a dispute resolution mechanism that is not only legalistic but also oriented towards sustainability and social justice.